Avaliação da efetividade de um curso de desenvolvimento de competências gerenciais - Oliveira Neto, Fernando Soares de (2011)
Dissertação (mestrado)-Universidade de Brasília, Instituto de Psicologia, 2009. === Submitted by Jaqueline Ferreira de Souza (jaquefs.braz@gmail.com) on 2011-06-17T19:27:26Z No. of bitstreams: 1 2009_FernandoSoaresONeto.pdf: 2254070 bytes, checksum: 7ea096d8e8307996a24ffae9ebbd5001 (MD5) === Approved for entry into archive by Jaqueline Ferreira de Souza(jaquefs.braz@gmail.com) on 2011-06-17T19:28:00Z (GMT) No. of bitstreams: 1 2009_FernandoSoaresONeto.pdf: 2254070 bytes, checksum: 7ea096d8e8307996a24ffae9ebbd5001 (MD5) === Made available in DSpace on 2011-06-17T19:28:00Z (GMT). No. of bitstreams: 1 2009_FernandoSoaresONeto.pdf: 2254070 bytes, checksum: 7ea096d8e8307996a24ffae9ebbd5001 (MD5) === Esta pesquisa teve por objetivo geral avaliar a efetividade de um curso para desenvolvimento de competências gerenciais e identificar variáveis que a predizem. O curso, de 128 horas-aula, foi oferecido a 256 executivos dos níveis hierárquicos mais altos do Banco Central do Brasil, dos quais 126 participaram da amostra. Como heteroavaliadores, participaram da pesquisa 68 subordinados desses gerentes. A pesquisa foi de natureza quantitativa, com delineamento correlacional de campo e pós-teste único. Os constructos utilizados foram impacto do treinamento no trabalho, em profundidade (transferência de treinamento relacionada aos conteúdos do curso) e em amplitude (desempenho posterior em dimensões mais amplas do cargo gerencial), além de suporte psicossocial à transferência. Foram construídos e validados instrumentos de coleta de dados para impacto em profundidade, auto e heteroavaliação e validados instrumentos de impacto em amplitude, auto e heterovaliação e suporte psicossocial à transferência de treinamento. Com o objetivo de mitigar o risco de ameaça à validade interna decorrente do delineamento, foi desenvolvida e associada aos questionários de impacto, somente na autoavaliação, uma segunda escala do tipo Likert, para medir o grau de contribuição do curso para a aquisição ou fortalecimento das competências. Para a análise de dados foram utilizadas técnicas de estatística descritiva e inferencial, incluindo análise fatorial e regressão padrão. Os resultados mostraram pequeno efeito do curso quanto ao impacto em profundidade e efeito um pouco maior em impacto em amplitude. Os escores da autoavaliação foram levemente superiores aos da heteroavaliação. A melhor preditora de impacto foi a variável suporte à transferência, mas, também, a variável tempo transcorrido desde o término do curso esteve correlacionada positivamente com impacto. A segunda escala adicionada aos questionários funcionou de forma adequada, ao oferecer uma medida aparentemente mais precisa da efetividade do curso. Pode-se considerar que o uso dessa última escala é uma alternativa para situações em que não se tenha oportunidade de tomar uma medida anterior à intervenção. ______________________________________________________________________________ ABSTRACT === The general objective of this study was to evaluate the impact of a managerial training program on the behavior of participants and indicate which variables predict this behavior. Brazilian as well as international literature show mixed results in relation to the effectiveness of general development courses. Organizations' interest in knowing the effects of TD&E on the performance of training program participants is increasing. Two hundred and fifty-six executives from the highest hierarchical levels of the Brazilian Central Bank finished this 128-hour course. The sample was composed of 126 executives and 68 of their subordinates (heteroevaluators). Deep impact, self, and heteroevaluation instruments were developed and validated for this quantitative study. Instruments that wTere developed by other researchers to measure the impact in amplitude, self, and heteroevaluatioii and psychosocial support for the transfer of training were also utilized. With the intent of minimizing the risk of tlireat to internal validity due to the design with only one posttest. the impact in depth and amplitude and self-evaluation questionnaires used two scales: one to measure the courses' degree of contribution towards the acquisition or strengthening of general competencies and another to measure the intensity of use of the same competencies. All the instruments used 5-point Likert scales. Data collection was done in two stages: the first with the participants and the second with the heteroevaluators. The electronic questionnaires were placed on an Internet site which was accessed through a link that had informed the participant by email about the training program, All of the seven scales used presented good psychometric indices (Cronbacb/s alfas between 0.86 and 0.98). Descriptive and inferential statistical techniques, including internal consistency analyses of the instruments, factor analysis, and standard multiple regression were used to analyze the data, The results show the course had a small effect as measured by the variables impact in depth (self and heteroevaluatioii) and a slightly larger effect on the impact in amplitude. The scales that measure the course's contribution in regards to the acquisition of the desired competencies presented smaller averages than the intensity of use scales, in both of the self-evaluations for impact. The best predictor of impact was the variable support for transfer, but the variable time since the training course ended also appeared, correlating positively with impact. The second scale added to the selfevaluation questionnaires of impact in depth and in amplitude performed adequately by offering an apparently more precise measure of the courses' effectiveness. The use of this scale can be considered an alternative for situations in which one does not have the opportunity to take certain measures before the intervention.